Failure analysis of compressed earth block using numerical plastic damage model (Fracture and Structural Integrity, 2022)
In the last decade, several studies have been introduced to the development and use of compressed earth blocks in green building construction. Studying the evaluation of existing cracks in construction builders by these blocks is an important industrial and safety subject in recent research. This objective opens a new field in building construction where we describe the mechanical behavior of compressed earth solid blocks. In addition, we offer a solution to rupture damages presented by the propagation of masonry cracks. This paper aims to explore a numerical study in ABAQUS where we analyze the mechanical properties of this block. We started by investigating the elastic phase for this material and it has been generalized to a study in the plastic regime and rupture for the studied block. The different results of numerical simulation of the studied shape are presented, compared, and criticized.
Keywords: Earth construction; Masonry buildings; HDPE; Rupture; Cracking; Integral J; Pressure; ABAQUS.; Inelastic strain; Compression strength; Crack direction